Depressiveness and Neuroticism in Bartonella Seropositive and Seronegative Subjects—Preregistered Case-Controls Study - Flegr, Jaroslav; Preiss, Marek; Balátová, Pavla (Frontiers in Psychiatry, 2018)
Several recent studies have demonstrated the association of cat-related injuries with major depression and with depressiveness in the general population. It was suggested that cat-scratch disease, the infection with the bacterium Bartonella henselae, can be responsible for the observed association. However, no direct evidence for the role of the Bartonella infection in this association has been published until now. In this preregistered case-controls study performed on 250 healthy subjects tested earlier for the presence of anti-Toxoplasma IgG antibodies, we searched for the positive association between presence of anamnestic anti-Bartonella IgG antibodies and depressiveness measured with Beck II inventory, depression subscale of neuroticism measured with N-70 questionnaire, and self-reported health problems. We found that that Bartonella-seropositivity was positively correlated with Beck depression only in Toxoplasma-seronegative men and negatively correlated with health in Toxoplasma-seronegative women. Bartonella seropositivity expressed protective effects against Toxoplasma seropositivity-associated increased neuroticism in men while Toxoplasma-seropositivity expressed protective effects against Bartonella seropositivity-associated health problems in women. A comparison of the patterns of association of mental and physical health problems with Bartonella seropositivity and with reported cat-related injury suggests that different factor, possibly infection with different pathogen transmitted by cat related-injuries than the Bartonella henselae, is responsible for the observed association of cat related-injuries with depressiveness and major depression. The existence of complex interactions between Bartonella seropositivity, Toxoplasma seropositivity, and sex also suggest that the effect of symbionts on the host’s phenotype must by always studied in the context of other infections, and separately for men and women.